Eksistensi Pengakuan Hak Masyarakat Hukum Adat Sasak atas Tanah di Kabupaten Lombok Utara - Opan Satria Mandala (CV Rewang Rencang, 2021)
The main problem of the existence of indigenous law communities has occurred since before Indonesia became independent until now, namely with the establishment of Land Management Rights by the government without being based on laws and regulations such as the mandate of the Indonesian Constitution. In fact, the existence & recognition of indigenous peoples has been recognized since before the independence phase of Indonesia. The arrangement regarding the recognition of the existence of indigenous law communities can be recognized because it is used as a basis in the preparation of the National Land Law. The author suggests that North Lombok Regency immediately formulate and issue a Regional Regulation with regard to the Recognition and Respect of “The Paer Rights”, especially with regard to the strengthening of Handlers (customary forests). Because the existence of this regulation has been a government policy; This conception should be turned into a common rule.